PROFESSIONAL TRAINING IN HEALTH, GENDER, AND CARE: INTERDISCIPLINARY AND CONTEMPORARY CHALLENGES - Nelson Martins Júnior, Leonidas; Cristina Vieira da Silva, Viviane; Maria da Silva Lira-Batista, Marta; Raulino de Barros, Emille; Lucas Viana Roly, Damião; Santos de Oliveira, Nathan (Revista Gênero e Interdisciplinaridade, 2026)
Professional health education faces significant challenges in addressing the complexity of care in contexts marked by social factors such as gender, race, class, and sexuality. This article presents a narrative literature review to analyze how training processes have (or have not) incorporated practices and knowledge geared towards comprehensive and equitable care. Based on the analysis of academic articles published between 2018 and 2023, two thematic categories were identified: (1) limitations and advances in health education focusing on equity and (2) care, identity, and the recognition of vulnerable populations. The findings highlight the persistence of traditional pedagogical models, with low inclusion of critical content on diversity and inequalities. In contrast, interdisciplinary experiences, participatory methodologies, and public policies focused on equity have emerged as promising strategies. It is concluded that overcoming inequalities in care necessarily requires critical, intersectional training committed to human rights and social justice.